Is Surgical Training Prepared for the “Second Wave” of COVID-19? A Collaborative Perspective - Harshadkumar Dhirajlal Rajgor, MRCS; Amarkumar Dhirajlal Rajgor, MRCS (ENT); Manpreet Singh Sidhu, MRCS; Shehzaad Aziz Khan, MRCS; Fahad Hossain, FRCS; Thomas Steven Moores, FRCS (Annals of Surgery Open, 2021)
Restructuring of surgical services during the ‘first wave’ of the coronavirus-disease 2019 pandemic led to significant disruption in surgical learning opportunities provided to junior surgeons. Recent challenges faced by trainees have never been faced before. These include disruption to surgical opportunities available, completing assessments and attending educational events. With a ‘second wave’ now upon the United Kingdom it is vitally important we reflect upon the ‘first wave’ to ensure junior surgeons are able to achieve appropriate surgical case numbers, complete assessments and progress to the next stage of training. Alternate assessment methods in the United Kingdom need to be considered should the pandemic continue and clear information should be provided to surgical trainees regarding career progression. These are difficult times for surgical training and we need to endeavor that trainees are provided with opportunities similar to their predecessors albeit in difficult circumstances. This is to ensure the future standard of surgical patient care remains of the highest standard.